Echocardiographic and physiological performance characteristics of triathletes - Claessen, C.; Claessens, P.; Claessens, M.; Claessens, J. (Canadian Journal of Cardiology, 2000)
BACKGROUND: Endurance sports require a variety of physiological adaptations. OBJECTIVE: To examine the structural and functional heart adaptations and their hemodynamic implications in triathletes. PATIENTS AND METHODS: A group of 52 male triathletes was compared with a control group of 22 healthy male nonathletes. All of the subjects were given a bidimensional cardiac Doppler echocardiography examination and administered maximal exercise tests with lactic acid determinations, on a bicycle ergometer and a treadmill. Results: The triathletes showed clear structural and functional heart adaptations with concentric and eccentric hypertrophy with evidence of a supernormal diastolic left ventricular function. The performance capacity of the triathlete differed significantly from that of the control subject. The maximal oxygen consumption and the maximal oxygen consumption per kilogram on the bicycle and on the treadmill were significantly higher in the triathletes. The same results and conclusions were obtained concerning aerobic capacities and power outputs on a bicycle ergometer at blood lactate concentrations of 2, 3 and 4 mmol/L. The heart rate 6 min after the start of exercise is a significant parameter for the evaluation of the physical condition of a subject. The lactic acid determinations during the recovery phase enabled important conclusions to be drawn about the physical condition of the subjects. CONCLUSIONS: The triathletes showed evidence of important structural and functional heart adaptations with hemodynamic implications. The maximal performing capacities, on the bicycle as well as on the treadmill, were distinctly higher in the triathlete group. Furthermore, the aerobic and anaerobic capacities were significantly different between the groups. In this context, the heart rate 6 min after the start of exercise and the blood lactate concentrations 20 min after the maximal exercise test were significant parameters. It was not always the best triathletes who had the most significant structural cardiac adaptations. Thus, the 'athletic heart' syndrome as a physiological entity is questioned. Can J Cardiol 2000 Aug;16(8):993-1002